Multibody mechatronic systems proceedings of the MUSME Conference held in Huatulco, Mexico, October 21-24, 2014 - MUSME (Conference) Huatulco, Mexico) 2014; Ceccarelli, Marco; Hernandez Martinez, Eusebio Eduardo; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
This volume contains the Proceedings of MUSME 2014, held at Huatulco in Oaxaca, Mexico, October 2014. Topics include analysis and synthesis of mechanisms; dynamics of multibody systems; design algorithms for mechatronic systems; simulation procedures and results; prototypes and their performance; robots and micromachines; experimental validations; theory of mechatronic simulation; mechatronic systems; and control of mechatronic systems. The MUSME symposium on Multibody Systems and Mechatronics was held under the auspices of IFToMM, the International Federation for Promotion of Mechanism and Mac.
Electronic reproduction.
Keywords: Mechatronics -- Congresses; Multibody systems -- Congresses; Electronic books